Implementasi Digital Saving Dalam Memperbaiki Mutu Layanan Pada Bank Rakyat Indonesia Kantor Cabang Jember - Sofi, Sofi; Putri Ayu (LAN TABUR : Jurnal Ekonomi Syariah, 2022)
This research aims to analyze the implementation of digital saving in improving service quality at the Bank Rakyat Indonesia Jember and identify how the obstacles, shortcomings and advantages of digital saving. The research method used a descriptive approach. informants use purposive technique. Data was collected by using observation, interview and documentation techniques. The results of the research show that digital savings at BRI KC Jember are implemented optimally through the website Bukarekening.bri.co.id which is in accordance with the theory of e-service quality. The obstacles experienced by BRI KC Jember are from internal and external factors. The internal factor has not been registered with the Civil Registration Office, thus hampering the process of creating a digital savings account. External factors used and the cellphone used by the customer is not supportive or the customer's cellphone memory is full. The drawback is that customers with new ID cards and old customers cannot create digital savings accounts. The advantage of digital savings is that Butaplus and Katplus are efficient without cards and transactions are faster. Keywords: Marketing Management, Digital Saving, Electronic Service Quality.